Management in Developing Students’ Entrepreneurship at Al-Hidayah Islamic Boarding School Jambi - Mardalina, Mardalina; Saleh, Ahmad Syukri; Widdah, Minna El (Yayasan Sembilan Pemuda Indonesia, 2025)
The objective of this research is to gather data on: 1) the communication management in developing students’ entrepreneurship; 2) the development of students’ entrepreneurship; 3) the supporting and inhibiting factors of communication management in developing students’ entrepreneurship; and 4) the communication management model for developing students’ entrepreneurship at Al Hidayah Islamic Boarding School in Jambi Province. The research approach used is descriptive-analytical research, a problem-solving procedure conducted by describing or illustrating the condition of the research object based on observable facts or as they are. Data collection instruments include observation, interviews, and documentation. Data analysis involves the process of Data Reduction, Data Presentation, and Drawing Conclusions. The technique for ensuring data validity is Data Triangulation. The research results show that the leadership successfully implemented communication management to develop students’ entrepreneurship through stages of planning, organizing, implementation, and evaluation using persuasive communication. The entrepreneurship development has progressed significantly, as seen in the growth of several business units. The supporting factors for communication management in developing students’ entrepreneurship include the credibility, authority, and charisma of the Islamic boarding school’s leadership. The communication management model for developing students’ entrepreneurship is a persuasive communication model based on the Symbolic Model.